2017
DOI: 10.1021/acschemneuro.7b00117
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Agonists for NMDA Receptor Glycine Binding Sites

Abstract: A series of analogues based on serine as lead structure were designed, and their agonist activities were evaluated at recombinant NMDA receptor subtypes (GluN1/2A–D) using two-electrode voltage-clamp (TEVC) electrophysiology. Pronounced variation in subunit-selectivity, potency, and agonist efficacy was observed in a manner that was dependent on the GluN2 subunit in the NMDA receptor. In particular, compounds 15a and 16a are potent GluN2C-specific superagonists at the GluN1 subunit with agonist efficacies of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
2
23
1
Order By: Relevance
“…Other features of GluN2C-containing receptors appear unique, raising the question of whether NMDA-Rs that contain this subunit have distinct structural conformations for some domains that differ from GluN2A, GluN2B, and GluN2D. For example, the ability of several glycine site agonists (Sheinin et al, 2001;Dravid et al, 2010;Maolanon et al, 2017) to enhance activity to levels above those observed for saturating glycine is unique to the GluN2C subunit, and unrelated to the glycine pocket, which resides within the GluN1 subunit. Thus, GluN2C could be a unique pharmacological target for modulation of thalamic and cerebellar circuits, where it is abundantly expressed (Akazawa et al, 1994;Karavanova et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other features of GluN2C-containing receptors appear unique, raising the question of whether NMDA-Rs that contain this subunit have distinct structural conformations for some domains that differ from GluN2A, GluN2B, and GluN2D. For example, the ability of several glycine site agonists (Sheinin et al, 2001;Dravid et al, 2010;Maolanon et al, 2017) to enhance activity to levels above those observed for saturating glycine is unique to the GluN2C subunit, and unrelated to the glycine pocket, which resides within the GluN1 subunit. Thus, GluN2C could be a unique pharmacological target for modulation of thalamic and cerebellar circuits, where it is abundantly expressed (Akazawa et al, 1994;Karavanova et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the enhancement of GluN2B subunits in CA1 could directly compensate for a lack of D-serine. GluN2A and GluN2B allosterically regulate co-agonist potency at the GluN1 glycine binding site (Priestley et al, 1995;Madry et al, 2007;Chen et al, 2008;Maolanon et al, 2017) with a two-to five-fold higher potency of co-agonists at GluN2B-containing NMDARs. Therefore, enhancement of GluN2B could compensate for a loss of D-serine given a smaller but stable pool of synaptic glycine.…”
Section: Regulation Of Ltp By Postsynaptic Serine Racemasementioning
confidence: 99%
“…There are two feasible ways of stimulating the glycine-binding site of the NMDA receptor, i.e., by direct stimulation of the glycine-binding site and by elevating the synaptic glycine levels. Agonists of the glycine-binding site of the NMDA receptors include glycine, D-serine, D-cycloserine, GLYX-13, vinyl glycine and a series of 3-acylamino-2-aminopropionic acid derivatives [79,80,81].…”
Section: Role Of the Nmda Receptors In Social Interactionmentioning
confidence: 99%